Belas Kasih Tanpa Batas: Refleksi Naratif-Teologis atas Lukas 10:25–37 dalam Konteks Kontemporer - Raulina, Raulina (Jurnal Teologi dan Pelayanan Kerusso, 2025)
In the context of a modern world increasingly marked by social fragmentation and individualistic tendencies, the parable of the Good Samaritan (Luke 10:25–37) offers a radical ethical vision regarding love and the identity of one's neighbor. This article aims to analyze the theological message of the parable using a narrative interpretation approach, particularly through an examination of narrative structure, characterization, and the dynamics of social reversal presented by the text. The study's findings indicate that love in this narrative is not merely an emotional response but a concrete action that involves courage across social, religious, and ethnic boundaries. This parable rhetorically challenges exclusive paradigms within the early readers' community of the Gospel of Luke and redefines the concept of "neighbor" from a passive object of compassion to an active subject who initiates love. These findings are relevant for contemporary society in efforts to build an ethics of solidarity across identities, as well as providing a theological foundation for inclusive and transformative practices of love amid a global humanitarian crisis.